Propelling a Learning Environment in Schools Significance of Principal and Teacher Leadership - Diwan, Rashmi (JOURNAL OF INDIAN EDUCATION, 2022)
The paper is centered on key leadership interventions in generating and sustaining environment conducive for learning in schools. The paper takes cognizance of creation of a positive culture to bridge the learning gaps, combat silent exclusion, addressing learning deficit in order to minimize school factors that hinder student learning. The paper also recommends changes a principal leader and teacher leader can bring in the overall school environment to facilitate student learning.